Trends in adolescent sexual and reproductive health communication campaigns (2007-2017): a review of dominant themes (2019)
This study, a content analysis of scholariy publications on adolescent sexual and reproductive health (ASRH) communication campaigns/interventions over a period of ten (10) years, adopted purposive and convenience sampling techniques to select 84 empirical studies on ASRH communication campaigns. While the unit of analysis was represented by keywords/'phrases. The content categories were teenage marriage. ASRH and the media, disease/pregnancy prevention strategies, socio-cultural issues and indicators of ASRH campaigns effects. These yielded 41 sub- categories and 704 frequency counts. Rogers Everett’s diffusion of innovations underpins the study and drives the research questions alongside extant literature. The study found that most of the studies, reporting an increase in pregnancy and H1V/AIDS spread recommended comprehensive ASRH education and campaign, where contraceptives are promoted alongside and/or against abstinence. lt was also discovered that community stakeholders’ resistance which was a common impediment to the success of comprehensive ASRH campaign has received scanty research attention, lt was therefore recommended that further research should be done on the relationship between campaign contents' themes. stakeholders resistance and globalization of ASRH messages. This, perhaps, would facilitate the understanding of the factors causing the unintended outcomes of ASRH